2011
DOI: 10.1007/s12610-011-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Amputation du gland au cours de la circoncision et réimplantation : à propos d’un cas et revue de la littérature

Abstract: Résumé L’amputation du gland au cours de la circoncision est une complication tragique dont la responsabilité incombe à l’opérateur. Le traitement de référence de cette lésion repose sur la réimplantation microchirurgicale par anastomose vasculaire et nerveuse. Nous rapportons un nouveau cas d’amputation totale du gland d’un enfant de six ans à la suite d’une circoncision et dont la réimplantation a été faite dans l’heure suivant l’accident, sans anastomose microchirurgicale. Avec un recul de plus de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…DIABATE [20] et al reported a case of successful glansal reimplantation of a patient admitted 15 minutes after amputation. ESSID [21] reported a case of amputation successfully reimplanted after a delay of 2 hours and a half.…”
Section: Discussionmentioning
confidence: 99%
“…DIABATE [20] et al reported a case of successful glansal reimplantation of a patient admitted 15 minutes after amputation. ESSID [21] reported a case of amputation successfully reimplanted after a delay of 2 hours and a half.…”
Section: Discussionmentioning
confidence: 99%